Farmers’ Willingness to Pay for Irrigation Water: A Case of Tank Irrigation Systems in South India - Karthikeyan Chandrasekaran (Water, 2009)
The economic value of tank irrigation water was determined through Contingency Valuation Method by analyzing farmers’ willingness to pay for irrigation water under improved water supply conditions during wet and dry seasons of paddy cultivation. Quadratic production function was also used to determine the value of irrigation water. The comparison of the economic value of water estimated using different methods strongly suggests that the present water use pattern will not lead to sustainable use of the resource in the tank command areas. Policy options for sustainable use of irrigation water and management of tanks in India were suggested.